2013
DOI: 10.4253/wjge.v5.i5.231
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of applying lidocaine in esophagogastroduodenoscopy performed under sedation with propofol

Abstract: Topical pharyngeal anaesthesia is safe in EGD but does not reduce the necessary dose of propofol or improve the anaesthetist's or endoscopist's satisfaction with the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…These findings compare favourably with those of prior studies by Sethi et al . and de la Morena et al . Sethi et al .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These findings compare favourably with those of prior studies by Sethi et al . and de la Morena et al . Sethi et al .…”
Section: Discussionmentioning
confidence: 94%
“…demonstrated that dexmedetomidine was a superior alternative to midazolam for conscious sedation in endoscopic retrograde cholangiopancreatography (ERCP). In the study of de la Morena et al ,. the same dose of propofol provided moderate sedation, which was defined as a score of 3 on the OAA/S during the EGD procedure.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, topical lidocaine pharyngeal anesthesia is a routine procedure, which gives the advantage of lubrication and less discomfort 17 . For patients who undergo esophagogastroduodenoscopy under propofol sedation, whether topical pharyngeal anesthesia is needed remains a controversial topic 18 . Additionally, the current guidelines on sedated endoscopy did not make any suggestions on this topic, which should be further examined in clinical research 8 .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] EGD can be performed in association with topical anesthesia of the pharynx, 5,6 intravenous anesthesia, [7][8][9] or with their combination. [10][11][12][13] EGD under topical pharyngeal anesthesia has the advantage of avoiding unwanted cardiopulmonary adverse events from intravenous sedationlike respiratory depression, cardiorespiratory arrest, especially in patients with cardiopulmonary disease, the elderly, and obese. [14][15][16] In Thailand, lidocaine spray is commonly used and is safe and easy in procedures requiring unsedated EGD.…”
Section: Introductionmentioning
confidence: 99%